Maxims and proverbs of oil Korea - Ha, Tae Hung. (Seoul : Yonsei University Press, 1972)
Includes 1,106 Korean proverbs presented in alphabetical order according to subject.
Parallel title in Korean characters.
In English and Korean.
Keywords: Maxims, Korean; Proverbs, Korean